Introduction: media and illiberal democracy in Central and Eastern Europe. Issue 1 (2nd January 2020) - Surowiec, Paweł; Štětka, Václav
ABSTRACT: This introductory overview opens the series of articles included in the issue entitled Media and Illiberal Democracy in Central and Eastern Europe, and sets the scene for the debate on the relationship between illiberal trends in politics and media landscapes in the region. Drawing on existing scholarship, it traces the roots and the evolution of illiberalism, focusing the discussion within the confines of particularities of media landscapes. Through the introduction of articles addressing manifestations of illiberalism in media landscapes, it argues that "illiberal turn" in Central and Eastern Europe is part of a global political shift, rather than a regional one.